FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERBANKAN DENGAN MENGGUNAKAN ECONOMIC VALUE ADDED BANK - Sharon, Sharon; Salim, Susanto (Jurnal Paradigma Akuntansi, 2024)
The research that has been conducted aims to obtain empirical evidence related to the effect of Bank Size, Capital Adequacy Ratio, Non Performing Loan, Loan to Deposit Ratio, and Board Size on Economic Value Added Bank in banking companies listed on the Indonesia Stock Exchange in the period 2017 to 2020. The research design used in this study was from the independent variable to the dependent variable to test the effect of the independent variable on the dependent variable used in the study. Purposive sampling method was used in this study. A total of 41 banks were used as research samples. In this study, the processing of data that has been collected using multiple linear regression analysis techniques is processed with SPSS version 26.0 software.The findings in this study showed that Bank Size had a significant positive effect on banking profitability (EVA). CAR and Board Size have a significant negative effect on banking profitability (EVA). NPL and LDR have no significant negative effect on banking profitability (EVA).